Money doctors : the experience of international financial advising, 1850-2000 - Flandreau, Marc. (London ; New York : Routledge, 2003)
The book shows that there is still a long way to go before international financial advice develops into something that is truly helpful in the long term
Includes bibliographical references and index.
gau 18/06/14
Loans
Keywords: International finance -- History; Monetary policy -- History; Financial planners -- History